A Luenberger-Like Observer for Multistable Kapitaniak Chaotic System. (14th July 2020) - Pérez-Cruz, J. Humberto; Allende Peña, Jacobo Marcos; Nwachioma, Christian; Rubio, Jose de Jesus; Pacheco, Jaime; Meda-Campaña, Jesus Alberto; Ávila-González, David; Guevara Galindo, Olivia; Adrian Romero, Ignacio; Belmonte Jiménez, Salvador Isidro
Abstract : The objective of this paper is to estimate the unmeasurable variables of a multistable chaotic system using a Luenberger-like observer. First, the observability of the chaotic system is analyzed. Next, a Lipschitz constant is determined on the attractor of this system. Then, the methodology proposed by Raghavan and the result proposed by Thau are used to try to find an observer. Both attempts are unsuccessful. In spite of this, a Luenberger-like observer can still be used based on a proposed gain. The performance of this observer is tested by numerical simulation showing the convergence to zero of the estimation error. Finally, the chaotic system and its observer are implemented using 32-bit microcontrollers. The experimental results confirm good agreement between the responses of the implemented and simulated observers.